Textile dyeing wastewater treatment by Penicillium chrysogenum: Design of a sustainable process - Ines Lanfranconi; María Belén Ceretta; Nora Bertola; Erika Alejandra Wolski; Ignacio Durruty (Water Science and Technology, 2022)
In this work a parametric study and a bench bioreactor degradation test of Direct Black 22 (DB22) by Penicillium chrysogenum was performed as a first approach to an industrial application, framed within a policy of sustainable processes development. Three ancillary carbon sources and their optimum initial concentrations were studied. These were: glucose, potato starch and potato industry wastewater. Their optimum initial concentration was 6 g/L. The use of potato starch as co-substrate showed the highest decolorization rate and COD removal. Degradation of DB22 using different immobilization supports (stainless steel sponge, loofah sponge and polyethylene strips) was studied and the results showed that the time needed for the treatment decreased from 6 to 4 d. Phytotoxicity was evaluated in the final products of the immobilized cells assays, using Lactuca sativa seeds. For all treatments phytoxicity was reduced with respect to the untreated wastewater, except for the assays using polyethylene strips. Finally, the reuse of the biomass attached to different carriers and the performance of the treatment of DB22 in a 1 L bench scale bioreactor were tested. P. chrysogenum decolorized at least four sucesives reuses. The reactor assays showed a better performance of the treatment. HIGHLIGHTS Penicillium chrysogenum shows good potential to decolorize the DB22 dye.; A parametric study of the biodegradation of an azo dye was performed to design a sustainable bioprocess.; Phytotoxicity of the dye was reduced after the treatment.; Biomass reuse and a bench bioreactor assay were successfully performed.;